28x-7y+13-18x-6-3y=

Simple and best practice solution for 28x-7y+13-18x-6-3y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 28x-7y+13-18x-6-3y= equation:


Simplifying
28x + -7y + 13 + -18x + -6 + -3y = 0

Reorder the terms:
13 + -6 + 28x + -18x + -7y + -3y = 0

Combine like terms: 13 + -6 = 7
7 + 28x + -18x + -7y + -3y = 0

Combine like terms: 28x + -18x = 10x
7 + 10x + -7y + -3y = 0

Combine like terms: -7y + -3y = -10y
7 + 10x + -10y = 0

Solving
7 + 10x + -10y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + 10x + -7 + -10y = 0 + -7

Reorder the terms:
7 + -7 + 10x + -10y = 0 + -7

Combine like terms: 7 + -7 = 0
0 + 10x + -10y = 0 + -7
10x + -10y = 0 + -7

Combine like terms: 0 + -7 = -7
10x + -10y = -7

Add '10y' to each side of the equation.
10x + -10y + 10y = -7 + 10y

Combine like terms: -10y + 10y = 0
10x + 0 = -7 + 10y
10x = -7 + 10y

Divide each side by '10'.
x = -0.7 + y

Simplifying
x = -0.7 + y

See similar equations:

| 5x-14+2x=76 | | 37x-4=23 | | X=15000-.25x | | 52=13b | | q^2+6q+8=0 | | -2.5(g-8)-0.7g= | | -1/3( | | g(x)=8+2x+e^2x-6 | | f^1(x)=4x^3+3x^2+3x+3 | | f-1(x)=4x^3+3x^2+3x+3 | | f(x)=4x^3+3x^2+3x+3 | | 70+81+77(2x)=85 | | 70+81+77+2x=85 | | 3(5x+8)=3x-2 | | -3(3j-1)+5j-1=3j-2 | | -3(2c+3)+2c-4=-2c+1 | | -3(2z-1)+2z+1=3z+1 | | (.25)(2)+x=.60 | | -3(-3a+4)+4a-3=3a+2 | | X^2-9x-42=0 | | -3(2d+3)-4d+2=3d-2 | | X^2-9x-42=I | | -10w^2+17w-12=0 | | x*1.06=13000 | | x*0.06=13000 | | -3x+1=.4x^2-x+1 | | 2x-3(26/9)=12 | | -x^2+50x=10x+175 | | 2(5/3)-3y=12 | | 15x+2=10x+3 | | 5/x=10/3 | | 2x+4(2-(5x-3))=20-18x |

Equations solver categories